MODERN LABORATORY BIOMARKERS OF BURN SEPSIS (LITERATURE REVIEW) - Akhmedov Rakhmatillo Furkatovich; Nurillayev Khasan Jamshid ugli (TADQIQOTLAR.UZ, 2024)
Abstract. Etiopathogenesis and diagnosis of sepsis is one of the controversial sections  of  combustiology,  due  to  the  difficult  diagnosis  and  the  possibility  of developing severe complications such as multiple organ failure.  Currently, there is no common view on the etiology, pathogenesis and diagnosis of burn sepsis.  In this article, the authors have undertaken to summarize the experience in the diagnosis of burn sepsis.  The opinions of various authors on the etiopathogenesis and diagnosis of this pathology are presented.